Emotion focused cognitive therapy - Power, Michael J.; Philippot, Pierre, 1960-; Hess, Ursula, 1960- (Chichester, UK. : Wiley-Blackwell, 2010)
'An academic text which clearly explains the theory of EFCT and its relationship with CBT. Provides a critique of CBT and other therapeutic approaches. Offers a summary of recent work on emotion, including an outline of the SPAARS approach. Written in an accessible manner, with trainee and practising therapists in mind. Presents the EFCT approach, with large numbers of clinical case examples summarised to reflect appropriate issues in working with emotions. Looks at the issues involved in working with problems related to the five basic emotions of fear, sadness, anger, disgust, and happiness'--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Emotion-focused therapy; Cognitive therapy